Defining the contribution of SNPs identified in asthma GWAS to clinical variables in asthmatic children - Tulah, Asif S.; Holloway, John W.; Sayers, Ian (BioMed Central, 2013)
Background: Asthma genome-wide association studies (GWAS) have identified several asthma susceptibility genes with confidence; however the relative contribution of these genetic variants or single nucleotide polymorphisms (SNPs) to clinical endpoints (as opposed to disease diagnosis) remains largely unknown. Thus the aim of this study was to firstly bridge this gap in knowledge and secondly investigate whether these SNPs or those that are in linkage disequilibrium are likely to be functional candidates with respect to regulation of gene expression, using reported data from the ENCODE project.